VARIASI MUSIMAN PRODUKSI SERASAH JENIS-JENIS DOMINAN HUTAN PEGUNUNGAN RENDAH DI TAMAN NASIONAL GUNUNG HALIMUN - JS Rahajoe; H Simbolon; T Kohyama (Research Center for Biology-Indonesian Institute of Sciences, 2004)
The litterfall of Allingia excelsa Noroflha, Schima wallichii (DC) Korth., Castanopsis acuminatissima (Bl.) A. DC, C. javanica (Bl.) A. DC. and Quercus lineata Blume, the dominant tree species of Lower Mountain at Gunung Halimun National Park - West Java were studied.The annual litterfall was 7.0 - 8.2 t ha y and the total litterfall was higher during the rainy season than in the dry season. Each dominant tree species had its own specific pattern of leaf shedding. A. excelsa shed their leaves at the end of the rainy season of the first year, during the biannual period of study, while Q. lineata was opposite.C.javanica shed their leaves mainly in the middle of the rainy season in January to February. There was no clear pattern of leaf shedding on C. acuminatissima,and the species was named as non-seasonally type, while S. wallichii, shed their leaves during the dry season, and was named as the dry season type.